ҚОРАҚАЛПОҒИСТОН ОЛИЙ ТАЪЛИМ МУАССАСАЛАРИДА ГЕНДЕР МАСАЛАСИНИ ЕЧИШНИНГ СТРАТЕГИЯСИ - Абдуллаева, Я.А. (SCIENCE and SOCIETY, 2022)
This article discusses the strategy for addressing gender issues in higher education institutions of Karakalpakstan. It is shown that the attitude towards women has become one of the priorities of state policy. Advisory boards established in higher education institutions pay special attention to youth and students. The activities of women’s advisory councils have been partially studied